Modernism in English and Uzbek Literature (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This article analyzes the role of the concept of modernism in literature, its main features, and how it is manifested in English and Uzbek literature. Modernism departs from traditional plot and forms of expression and is based on such methods as the complexities of human consciousness, the relativity of time and reality, symbolism, and internal monologue. The article compares the elements of modernism in both literatures and reveals their unique aspects.